High Ozone (O3) Affects the Fitness Associated with the Microbial Composition and Abundance of Q Biotype Bemisia tabaci - Hong, Yanyun; Yi, Tuyong; Tan, Xiaoling; Zhao, Zihua; Ge, Feng (Frontiers in Microbiology, 2016)
Abstract Ozone (O3) affects the fitness of an insect, such as its development, reproduction and protection against fungal pathogens, but the mechanism by which it does so remains unclear. Here, we compared the fitness (i.e., the growth and development time, reproduction and protection against Beauveria bassiana (B. bassiana) of Q biotype whiteflies fumigated under hO3 (280 ± 20 ppb) and control O3 (50 ± 10 ppb) concentrations. Moreover, we determined that gene expression was related to development, reproduction and immunity to B. bassiana and examined the abundance and composition of bacteria and fungi inside of the body and on the surface of the Q biotype whitefly. We observed a significantly enhanced number of eggs that were laid by a female, shortened developmental time, prolonged adult lifespan, decreased weight of one eclosion, and reduced immunity to B. bassiana in whiteflies under hO3, but hO3 did not significantly affect the expression of genes related to development, reproduction and immunity. However, hO3 obviously changed the composition of the bacterial communities inside of the body and on the surface of the whiteflies, significantly reducing Rickettsia and enhancing Candidatus_Cardinium. Similarly, hO3 significantly enhanced Thysanophora penicillioides from the Trichocomaceae family and reduced Dothideomycetes (at the class level) inside of the body. Furthermore, positive correlations were found between the abundance of Candidatus_Cardinium and the female whitefly ratio and the fecundity of a single female, and positive correlations were found between the abundance of Rickettsia and the weight of adult whiteflies just after eclosion and immunity to B. bassiana. We conclude that hO3 enhances whitefly development and reproduction but impairs immunity to B. bassiana, and our results also suggest that the changes to the microbial environments inside of the body and on the surface could be crucial factors that alter whitefly fitness under hO3. Key words: Bemisia tabaci, high ozone (hO3), fitness, microbial communities, inside of the body, on the surface